Panorama Francophone Student Book 1 Student Book 1 - Danièle Bourdais (Cambridge advance Materials, 2014)
Designed to prepare students for the Ab Initio French course for the IB Language B programme, it is the first of two coursebooks covering the two year course. International in approach and containing material designed to engage older teenage learners, it requires students to think and reflect at a level that is suitable for an IB Diploma student. There is a strong emphasis on developing intercultural understanding, as well as French as a world language, with francophone culture taking a central role. All language is taught and practised in context, and ToK and CAS are fully integrated into the learning.
Keywords: MY - French